pH-mediated control over the mesostructure of ordered mesoporous materials templated by polyion complex micelles - Molina, Emilie; Mathonnat, Mélody; Richard, Jason; Lacroix-Desmazes, Patrick; In, Martin; Dieudonné, Philippe; Cacciaguerra, Thomas; Gérardin, Corine; Marcotte, Nathalie (Beilstein Journal of Nanotechnology, 2019)
Ordered mesoporous silica materials were prepared under different pH conditions by using a silicon alkoxide as a silica source and polyion complex (PIC) micelles as the structure-directing agents. PIC micelles were formed by complexation between a weak polyacid-containing double-hydrophilic block copolymer, poly(ethylene oxide)-b-poly(acrylic acid) (PEO-b-PAA), and a weak polybase, oligochitosan-type polyamine. As both the micellization process and the rate of silica condensation are highly dependent on pH, the properties of silica mesostructures can be modulated by changing the pH of the reaction medium. Varying the materials synthesis pH from 4.5 to 7.9 led to 2D-hexagonal, wormlike or lamellar mesostructures, with a varying degree of order. The chemical composition of the as-synthesized hybrid organic/inorganic materials was also found to vary with pH. The structure variations were discussed based on the extent of electrostatic complexing bonds between acrylate and amino functions and on the silica condensation rate as a function of pH.
Keywords: double-hydrophilic block copolymer; hybrid organic–inorganic interface; mesoporous materials; nanostructured materials; polyion complex micelles; polyion electrostatic complexation